水蒸気プロセスにより作製したアルミニウム合金表面の層状複水酸化物皮膜の透過電子顕微鏡観察 - 小橋, 眞; 嶋田, 雄太; 李, 鴻美; 石崎, 貴裕; 高田, 尚記; 芹澤, 愛 (鉄と鋼, 2019)
Microstructures and crystallographic features of layered double hydroxide (LDH) particles and the LDH film formed on the aluminum alloy sheet (alloy 7075) using the steam coating process were examined by transmission electron microscopy (TEM). The LDH powder particles exhibited a hexagonal-disc-shape morphology. Their disc plane and side planes were parallel to a basal plane and prism planes of the LDH hexagonal crystal, respectively. A cross-sectional thin TEM sample was prepared from the interface between the LDH film and the Al alloy substrate using a focused ion beam combined with pick-up technique. TEM observations revealed that the LDH film formed on the Al alloy exhibited a dual-layer structure, which consists of a continuous Zn-rich amorphous layer (including numerous nano-particles with fcc structure) on the Al substrate side and a LDH layer composed of a number of disc-shaped LDH particles.